Experimental Research on Mechanical Properties of Frozen Sands under Isotropic Compression Conditions. Issue 5 (September 2019) - Luo, Fei; Lei, Jian; Lv, Siqing; Xi, Yuxuan; Song, Zhijie; Zhang, Junkai
Abstract: The K-G model has better practicability and superiority than the E-μ model. Conventional triaxial tests of frozen sand samples were carried out at -10 C under confining pressures of 0.5 MPa, 1.0 MPa, 2.0 MPa, 4.0 MPa and 6.0 MPa. During the consolidation process, the samples behave an isobaric state. While the confining pressure σ3 is unchanged, axial pressure σ1 is gradually increased during the shearing process. The test results show that the volumetric strain increases nonlinearly with the increase of the volumetric stress in the isobaric state, showing a power function trend. An improved K-G model is proposed to describe strain softening of frozen sand during shear. The verification results show that the model has good applicability.